THE MULTIDISCIPLINARY TREATMENT OF THE PATIENT WITH ORAL CANCER: a literature review. - Lacerda, Jamille dos Passos; Ribeiro, Joseana Moreira Assis; Fernandes, Karoline Maciel; Gomes , Cibele Avila; Silva, Orlany Maria dos Santos; Machado, Raquel Ribeiro; Reis, Jeferson Fernando Barbosa dos; Cunha , Julia Marins (Brazilian Journal of Implantology and Health Sciences, 2023)
The objective of this article is to carry out a survey of the current medical literature on the relationship between interdisciplinarity in the care of patients with oral cancer. A search was performed on the Google Scholar database using the keywords “Oral cancer, Multidisciplinary treatment, Dentistry, Medicine, Nursing, Physiotherapy, Nutrition”. Articles with more than 20 years of publication or that did not fit the scope of the research were excluded. In all, 17 articles that fit the search patterns were selected. It is concluded that multi and interdisciplinary treatment is the best option for the treatment of patients with oral cancer.